Evaluation of Insecticidal Performances of Jayanti Plant (Sesbania sesban) for Integrated Control of Cabbage Caterpillar (Plutella xylostella) - Suripto Suripto; Lalu Japa; Hilman Ahyadi; Rachmawati Noviana Rahayu (Jurnal Penelitian Pendidikan IPA, 2023)
The study on the use of local natural materials as a source of insecticides is intended, among other things, to reduce farmers' dependency on using synthetic chemicals. This research was conducted to obtain the most selective insecticidal active ingredient from Sesbania sesban plant for controlling cabbage caterpillars, choose a target mode of action that has a safe impact on the environment, and determine insecticidal stability during storage of the material prior to application and its stability in water after application.Â  The dried powder of S. sesban leaves was extracted in stages using a series of solvents, namely hexane, DCM, ethanol and water, respectively.Â  Each of the extract fractions produced was tested for its lethal toxicity against Plutella xylostella larvae and Diadegma semiclausum imago. Each of mortality data were processed by probit analysis to produce LC50(s) to determine their insecticidal selectivity. Subsequent bioassays were carried out using extract-water of S. sesban leaves and the data were processed by probit analysis to determine their anti-ovipositor, ovicidal powers and anti-feedant properties against P. xylostella. The insecticidal stability of S. sesban was also studied according to variations in the storage time of the simplicia before extraction, the storage time of the extract before dissolution, and its stability in water during application. The data was processed using ANOVA. The results show that the insecticidal activity of the ethanol extract fraction of S. sesban leaves for controlling cabbage caterpillars was very selective, namely very toxic to P. xylostella but very less toxic to D. semiclausum. Against P. xylostella, S. sesban leaf extract has also been proven to significantly prevent oviposition, inhibit egg hatching and feeding activity. The insecticidal power of S. sesban did not decrease significantly during storage of the simplicia for less than three months and during storage of the extract for less than seven days. However, the toxicity of the extract solution decreased drastically after 24 hours of application